Unobtrusive Multimodal Biometric Authentication: The HUMABIO Project Concept. (9th March 2008) - Damousis Damousis, Ioannis G. Ioannis G.; Tzovaras Tzovaras, Dimitrios Dimitrios; Bekiaris Bekiaris, Evangelos Evangelos
Abstract : Human Monitoring and Authentication using Biodynamic Indicators and Behavioural Analysis (HUMABIO) (2007) is an EU Specific Targeted Research Project (STREP) where new types of biometrics are combined with state of the art sensorial technologies in order to enhance security in a wide spectrum of applications. The project aims to develop a modular, robust, multimodal biometrics security authentication and monitoring system which utilizes a biodynamic physiological profile, unique for each individual, and advancements of the state-of-the art in behavioural and other biometrics, such as face, speech, gait recognition, and seat-based anthropometrics. Several shortcomings in biometric authentication will be addressed in the course of HUMABIO which will provide the basis for improving existing sensors, develop new algorithms, and design applications, towards creating new, unobtrusive biometric authentication procedures in security sensitive, controlled environments. This paper presents the concept of this project, describes its unobtrusive authentication demonstrator, and reports some preliminary results.